2015
DOI: 10.5935/1518-0557.20150029
|View full text |Cite
|
Sign up to set email alerts
|

AMH as a Prognostic Factor for Blastocyst Development

Abstract: We conclude that patients that were considered eligible to undergo blastocyst formation have higher levels of serum AMH, however too high concentration of this hormone can be harmful to blastocyst development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…The latter group of women is similar to the population enrolled in our study, and hence the results may be considered to be in agreement (Lie Fong et al, 2008). Perhaps one of the most controversial findings in our study was that AMH levels correlated with embryo quality, as reported by De Conto et al (2015); however, since our population was small, the quality A blastocyst higher pregnancy rate was not significantly different. It should also be mentioned that some authors have described AMH as a weak predictor for clinical pregnancy, which may explain why we found no differences between pregnancy rates in our results (Tal et al, 2015;Umarsingh et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The latter group of women is similar to the population enrolled in our study, and hence the results may be considered to be in agreement (Lie Fong et al, 2008). Perhaps one of the most controversial findings in our study was that AMH levels correlated with embryo quality, as reported by De Conto et al (2015); however, since our population was small, the quality A blastocyst higher pregnancy rate was not significantly different. It should also be mentioned that some authors have described AMH as a weak predictor for clinical pregnancy, which may explain why we found no differences between pregnancy rates in our results (Tal et al, 2015;Umarsingh et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…Perhaps one of the most controversial findings in our study was that AMH levels correlated with embryo quality, as reported by De Conto et al . (2015) ; however, since our population was small, the quality A blastocyst higher pregnancy rate was not significantly different.…”
Section: Discussionmentioning
confidence: 47%
“…The difference in pregnancy outcomes among blastocyst groups may be related to serum AMH concentrations. Scheffer et al and De Conto et al showed that serum AMH concentration was related to embryo development and blastocyst formation, but too high or too low AMH concentration was not conducive to blastocyst formation (12,13). In our study, AMH in HQB-D5 was significantly higher than in LQB groups regardless of D5 or D6, suggesting that it was related to the quality of the blastocysts formed.…”
Section: Discussionsupporting
confidence: 42%
“…AMH has been shown to predict oocyte morphology, fertilization, blastocyst formation, implantation, and pregnancy rates [5,19,20]. Borges et al (2017) found that, in a sample of 4488 oocytes from 408 patients, AMH was predictive of embryo morphology on day 2 and day 3, fertilization and blastocyst formation, implantation rates, and clinical pregnancy rates after adjusting for age [5].…”
Section: Introductionmentioning
confidence: 99%